Laboratory Logistics: Strategies for Integrating Information Literacy Instruction into Science Laboratory Classes. - Kathleen Gregory (Issues in Science and Technology Librarianship)
Active learning is a hallmark of the traditional science laboratory class, making it a natural place for librarians to integrate active information literacy instruction. The course structure of science lab classes, particularly large entry-level undergraduate classes, can make the logistics of such integration a challenge. This paper presents two case studies, each highlighting a different method of providing information literacy instruction to large undergraduate science classes for non-majors. In the first, teaching assistants helped to provide instruction within scheduled lab periods; in the second, a set number of workshops occurred outside of the regular meeting times of the lab classes. To measure the success of these strategies, instructors, teaching assistants, and students provided formal and informal feedback. Evaluation of these results points to a third possible strategy for integrating library instruction into science lab classes. Moving librarian-led instruction online and reserving class time for activities mediated by teaching assistants may solve many of the logistical challenges to teaching information literacy in science labs. [ABSTRACT FROM AUTHOR]